Knowledge management strategy formulation at local government level : the case of the City of Ekurhuleni Metropolitan Municipality - Mahlaule, Nyeleti Stella (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.